Biome geo facts - Howell, Izzi (Geofacts (Crabtree Publishing Company), 2018)
Highlights the various biomes found on the planet from rain forests and grasslands to deserts and tundras. Includes maps, a glossary, text-related questions, resources for further information, and color photographs.